Collaborating to prepare students for perioperative nursing - Lacey, Kimberly; Forte, Pamela; Tammaro, Marie (Nurse Educator, 2024)
An abstract is unavailable.
Keywords: dept.nur; peer-reviewed

Transforming clinical faculty preparation: A multistudent, multipatient simulation for nurse educator students - Kulacz, Regina; Lamberti, Amanda; Forte, Pamela; Lacey, Kimberly (Clinical Simulation in Nursing, 2026)
Keywords: Clinical Practice; Clinical faculty; Clinical judgment; Faculty development; Graduate students; Multipatient; Multistudent; Nurse education; Nurse educator; Nursing; Postgraduate; Role transition; Simulation; Student nurse; dept.nur

An Innovative Academic/Practice Partnership to Support Nursing Workforce Needs and Student Clinical Education - Hahn, Judith; Resha, Cheryl-Ann; Beauvais, Audrey; Beckman, Beth; Forte, Pamela; Rebeschi, Lisa M.; Snyder, Marianne (JONA: The Journal of Nursing Administration, 2023)
Innovation is needed to solve nursing workforce issues during times of crisis. A collaborative effort between a hospital system and several universities resulted in the Bridge to Professional Practice Program that was implemented during a period of high patient volume and nursing student downtime. The program provided support for staffing needs and clinical hours to promote readiness for practice for students. The program evaluation outcomes and recommendations for improvement are addressed.
Keywords: dept.nur; peer-reviewed

After the gap analysis: Education and practice changes to prepare nurses of the future - Beauvais, Audrey Marie; Kazer, Meredith Wallace; Aronson, Barbara; Conlon, Suzanne E.; Forte, Pamela; Fries, Kathleen S.; Hahn, Judith M.; Hullstrung, Russell; Levvis, Meg; McCauley, Paula; Morgan, Patricia Padula; Perfetto, Linda; et al. (Nursing Education Perspectives, 2017)
AIM The purpose of the study was to describe the Connecticut Nursing Collaborative-Action Coalition’s work in identifying and addressing gaps between nursing education and practice based on the Institute of Medicine’s Future of Nursing report. BACKGROUND Massachusetts Nurse of the Future (NOF) Competencies highlight the knowledge, skills, and attitudes/behaviors required for professional nurses. Integrating these concepts into the educational system will prepare the nursing workforce to respond to current/future health care needs and population health issues. METHOD Education and practice partners in four regions conducted a gap analysis of the education to practice transition for new graduate nurses using NOF as a framework for assessment. RESULTS Gaps in competencies were similar across regions. However, each organization uniquely addressed curricular gaps to best prepare nurses of the future. CONCLUSION Curriculum improvements will provide students the advantage of being prepared for the rapid changes happening in health care. Copyright © 2017 National League for Nursing
4 citations (Crossref) [2023-10-31]
Keywords: Academic-Practice Partnership; Connecticut; Curriculum; Education; Nursing; Forecasting; Future of Nursing Competencies; Gap Analysis; Humans; Massachusetts; New Graduate Nurses; Nursing Curriculum; Nursing Education; Nursing Staff; article; curriculum; dept.nur; forecasting; health care need; human; human experiment; nursing education; nursing staff; peer-reviewed; population health; skill; student; workforce